2015
DOI: 10.3109/1354750x.2015.1118536
|View full text |Cite
|
Sign up to set email alerts
|

Circulating resistin is a significant predictor of mortality independently from cardiovascular comorbidities in elderly, non-diabetic subjects with chronic kidney disease

Abstract: Elevated circulating resistin was a significant independent predictor of CV and all-cause mortality in elderly, non-diabetic CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 39 publications
0
17
0
2
Order By: Relevance
“…Although the specific mechanisms remain unknown, resistin may be involved in the progression of cardiovascular disease by stimulating inflammation [ 16 ]. Previously published clinical studies have shown that plasma resistin levels were significantly associated with risk factors and adverse clinical outcomes in cardiovascular disease, which further supports a role for resistin and its associated signaling pathways in cardiovascular disease [ 17 ].…”
Section: Discussionmentioning
confidence: 67%
“…Although the specific mechanisms remain unknown, resistin may be involved in the progression of cardiovascular disease by stimulating inflammation [ 16 ]. Previously published clinical studies have shown that plasma resistin levels were significantly associated with risk factors and adverse clinical outcomes in cardiovascular disease, which further supports a role for resistin and its associated signaling pathways in cardiovascular disease [ 17 ].…”
Section: Discussionmentioning
confidence: 67%
“…GFR was calculated using the formula CKD-EPI (ml/min/1.73 m 2 ). The degree of decline in GFR was assessed in accordance with the recommendations of 2015 [4]. The value of the microalbuminuria and VEGF was determined in the morning portion of urine.…”
Section: Methodsmentioning
confidence: 99%
“…Adipokines, especially leptin and resistin, are associated with insulin resistance, obesity, and hypertension with renal disease [4]. Leptin stimulates the growth of glomerular, mesangial cells owing to activation by growth factors, including VEGF [5].…”
Section: Introductionmentioning
confidence: 99%
“…В настоящее время высказываются предположения о провоспалительной направленности его действия при хронической болезни почек (ХБП) наравне с хемерином и рядом других адипокинов [2,3]. Уровень резистина в крови выше у пациентов с ХБП по сравнению со здоровыми лицами [4], а его значение более 127,4 нг/мл является независимым фактором риска смерти больных на гемодиализе [5] и при недиабетической ХБП у пожилых пациентов [6]. В настоящее время роль резистина в патогенезе хронического гломерулонефрита не изучена, и проведено пока очень мало исследований по взаимосвязи резистина с клиническими и морфологическими параметрами данной патологии.…”
Section: Introductionunclassified